On the Behaviour of a Human Serum Proactivator Reacting with Streptokinase during Artificial Activation of the Fibrinolytic System - Doleschel, W; Auerswald, W (Thrombosis and Haemostasis, 1961)
During “spontaneous” activation of a human euglobulin preparation in suitably spaced samples — while plasminogen became progressively converted into piasmin — the proactivator content was tested by addition of equal amounts of streptokinase and evaluation of the lytic activities on heated and normal bovine fibrin plates. Indepedently of the decreasing content of plasminogen the proactivator which could be activated by streptokinase showed no significant change of concentration. These observation indicate that plasminogen is not acting as proactivator and that there exists a separate proactivator-activator system of the fibrinolytic mechanism in human serum.